Concise Bible doctrines - Towns, Elmer L. (Chattanooga, TN: AMG Publishers, 2006)
Contents: Introduction. Understanding Christianity ; Understanding faith -- Understanding the doctrine of the Bible. Revelation ; Inspiration ; Inerrancy and canonicity ; How to interpret the Bible -- Understanding the doctrine of God. Who God is ; The attributes of God ; The law of God ; The work of God ; The Trinity ; The Father ; The names of God -- Understanding the doctrine of Christ. The preexistence of Christ ; The offices of Christ ; The virgin birth ; How Christ became a man ; The perfection of Christ ; The death of Jesus Christ ; The atonement ; The resurrection ; The ascension of Christ ; The present ministry of Jesus Christ -- Understanding the doctrine of the Holy Spirit. The person of the Holy Spirit ; The present ministry of the Holy Spirit -- Understanding the doctrine of man. The nature of man ; The freedom of man ; The personality of man ; The fall of man ; The nature of sin -- Understanding the doctrine of salvation. Conversion and regeneration ; Our position -- Understanding the doctrine of angels. The nature of angels ; The works of angels -- Understanding the doctrine of Satan. The nature of Satan ; The works of Satan -- Understanding the doctrine of demons. Demons ; Demon activity -- Understanding the doctrine of the church. The nature of the church ; Church membership ; The aims of the church ; Church leadership ; Church government ; The ordinances of the church -- Understanding the doctrine of last things. The nature of prophecy ; The signs of the times ; The rapture ; The tribulation ; The millennium ; The judgments ; The eternal abode of the unsaved ; The eternal home of the saved.
Keywords: Theology, Doctrinal -- Popular works